Corruption and Elites in Late Antiquity: The Case of Quintus Aurelius Symmachus - Matej Petrič (Keria: Studia Latina et Graeca, 2018)
The paper presents the many corrupt or suspect practices encountered by Quintus Aurelius Symmachus, a prominent senator of the late 4th century, in his capacity as city prefect (384/5). These practices afford some insight into the functioning of Late Antique interest-based networks, which enabled individuals or groups to influence and hamper the work of the imperial administration.